2010
DOI: 10.1039/c0sc00451k
|View full text |Cite
|
Sign up to set email alerts
|

N-heterocyclic carbenes which readily add ammonia, carbon monoxide and other small molecules,

Abstract: N-Heterocyclic carbenes (NHCs) are extremely valuable as nucleophilic organocatalysts. They are widely applied as ligands in transition-metal catalysed reactions, where they are known as particularly potent s-donors. They are commonly viewed as workhorses exhibiting reliable, but undramatic, chemical behaviour. The N / C carbene p-donation stabilises NHCs at the expense of low reactivity towards nucleophiles. In contrast to NHCs, stable (alkyl)(amino)carbenes exhibit spectacular reactivity, allowing, for examp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
90
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(95 citation statements)
references
References 51 publications
3
90
0
2
Order By: Relevance
“…[10] Theaddition of gaseous NH 3 to aC 6 D 6 solution of 1o produced no noticeable change,a sd etermined by 1 HNMR spectroscopy. [10] Building on these results,w er easoned that the capture and subsequent release of NH 3 over the course of as ingle experiment should be possible by utilizing the distinct electronic states of 1.T otest this hypothesis,aC 6 D 6 solution of 1o was transferred to aq uartz low-pressure NMR tube equipped with aT eflon screw cap and cooled to À78 8 8C. [10] Building on these results,w er easoned that the capture and subsequent release of NH 3 over the course of as ingle experiment should be possible by utilizing the distinct electronic states of 1.T otest this hypothesis,aC 6 D 6 solution of 1o was transferred to aq uartz low-pressure NMR tube equipped with aT eflon screw cap and cooled to À78 8 8C.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…[10] Theaddition of gaseous NH 3 to aC 6 D 6 solution of 1o produced no noticeable change,a sd etermined by 1 HNMR spectroscopy. [10] Building on these results,w er easoned that the capture and subsequent release of NH 3 over the course of as ingle experiment should be possible by utilizing the distinct electronic states of 1.T otest this hypothesis,aC 6 D 6 solution of 1o was transferred to aq uartz low-pressure NMR tube equipped with aT eflon screw cap and cooled to À78 8 8C. [10] Building on these results,w er easoned that the capture and subsequent release of NH 3 over the course of as ingle experiment should be possible by utilizing the distinct electronic states of 1.T otest this hypothesis,aC 6 D 6 solution of 1o was transferred to aq uartz low-pressure NMR tube equipped with aT eflon screw cap and cooled to À78 8 8C.…”
mentioning
confidence: 88%
“…[3] We recently developed ap hotoswitchable NHC by incorporating ap hotochromic [4] dithienylethene (DTE) [5] unit into an imidazolylidene backbone,and found that the corresponding carbene functioned as ap hotoswitchable organocatalyst for transesterification and transamidation [6] reactions as well as for ring-opening polymerizations. [10] Herein, we report the first isolable,p hotoswitchable NHC and demonstrate the remote modulation of its electronic properties in the free carbene state as well as its utility in the on-demand capture and release of ammonia. [8] All of these catalysts were effectively switched between "off" (inactive) and "on" (active) states by irradiation with UV or visible light, respectively.A lthough other DTE-functionalized NHCs have been reported, [9] the corresponding free carbenes have hitherto not been isolable and required in situ generation.…”
mentioning
confidence: 93%
“…[1,15] Among the first examples of highly reactive main-group species that are able to activate stable molecules were carbenes (B,S cheme 1), featuring electron-rich, two-coordinate carbon centers. [16,17] Theh eavier Group 14 homologues,s ilylenes and germylenes,w ere also investigated;f or example,M üller et al reported on the activation of dihydrogen whereas Roesky et al investigated the addition of ammonia to silylenes. [16,17] Theh eavier Group 14 homologues,s ilylenes and germylenes,w ere also investigated;f or example,M üller et al reported on the activation of dihydrogen whereas Roesky et al investigated the addition of ammonia to silylenes.…”
mentioning
confidence: 99%
“…21b,25 A similar mechanism can be invoked to explain the formation of the 1,2-azaboretidine, since the initial reduction of 3a presumably yields a high-energy borylene (ADC = B–Dur), analogous to the aforementioned ketene (ADC = CO).…”
Section: Resultsmentioning
confidence: 97%